Mechanosensory Signaling in Enterochromaffin Cells and 5-HT Release: Potential Implications for Gut Inflammation - Linan-Rico, Andromeda; Ochoa-Cortes, Fernando; Beyder, Arthur; Soghomonyan, Suren; Zuleta-Alarcon, Alix; Coppola, Vincenzo; Christofi, Fievos L. (Frontiers in Neuroscience, 2016)
Enterochromaffin cells (EC) synthesize 95% of the body 5-HT and release 5-HT in response to mechanical or chemical stimulation. EC cell 5-HT has physiological effects on gut motility, secretion and visceral sensation. Abnormal regulation of 5-HT occurs in gastrointestinal disorders and Inflammatory Bowel Diseases (IBD) where 5-HT may represent a key player in the pathogenesis of intestinal inflammation. The focus of this review is on mechanism(s) involved in EC cell ‘mechanosensation’ and critical gaps in our knowledge for future research. Much of our knowledge and concepts are from a human BON cell model of EC, although more recent work has included other cell lines, native EC cells from mouse and human and intact mucosa. EC cells are ‘mechanosensors’ that respond to physical forces generated during peristaltic activity by translating the mechanical stimulus (MS) into an intracellular biochemical response leading to 5-HT and ATP release. The emerging picture of mechanosensation includes Piezo 2 channels, caveolin-rich microdomains and tight regulation of 5-HT release by purines. The ‘purinergic hypothesis’ is that MS releases purines to act in an autocrine / paracrine manner to activate excitatory (P2Y1, P2Y4, P2Y6, A2A/A2B) or inhibitory (P2Y12, A1, A3) receptors to regulate 5-HT release. MS activates a P2Y1/Gαq/PLC/IP3-IP3R/SERCA Ca2+signaling pathway, an A2A/A2B–Gs/AC/cAMP-PKA signaling pathway, an ATP-gated P2X3 channel, and an inhibitory P2Y12 -Gi/o/AC-cAMP pathway. In human IBD, P2X3 is down regulated and A2B is up regulated in EC cells, but the pathophysiological consequences of abnormal mechanosensory or purinergic 5-HT signaling remain unknown. EC cell mechanosensation remains poorly understood.